2021
DOI: 10.1111/obr.13152
|View full text |Cite
|
Sign up to set email alerts
|

Interventions using behavioural insights to influence children's diet‐related outcomes: A systematic review

Abstract: The global prevalence of children with overweight and obesity continues to rise. Obesity in childhood has dire long-term consequences on health, social and economic outcomes. Promising interventions using behavioural insights to address obesity in childhood have emerged. This systematic review examines the effectiveness and health equity implications of interventions using behavioural insights to improve children's diet-related outcomes. The search strategy included searches on six electronic databases, refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In the primary school setting (aged 5-12 years), the same Click & Crunch intervention was found to be effective at improving healthy food purchases by primary school students at 18 months (+3.8% “everyday” and –2.6% “less healthy” items purchased) [ 29 ]. Such findings demonstrate the potential merit of the Click & Crunch intervention on improving the nutritional quality of both primary and high school student online lunch purchases over both the short and longer term and challenge the previously held notion that choice architecture interventions may attenuate over time due to their “novelty effect” or “label fatigue” experienced by end users [ 10 ].…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…In the primary school setting (aged 5-12 years), the same Click & Crunch intervention was found to be effective at improving healthy food purchases by primary school students at 18 months (+3.8% “everyday” and –2.6% “less healthy” items purchased) [ 29 ]. Such findings demonstrate the potential merit of the Click & Crunch intervention on improving the nutritional quality of both primary and high school student online lunch purchases over both the short and longer term and challenge the previously held notion that choice architecture interventions may attenuate over time due to their “novelty effect” or “label fatigue” experienced by end users [ 10 ].…”
Section: Discussionmentioning
confidence: 66%
“…This is the first study to assess the long-term effectiveness of an intervention embedded within an online lunch ordering system for high school students and is one of few studies to assess the long-term effectiveness of food choice architecture interventions more broadly [ 10 , 23 , 24 ]. The Click & Crunch High Schools cluster RCT found that intervention students, relative to control, ordered significantly more healthy “everyday” items and significantly fewer “less healthy” items from baseline to 15-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations